Self-reported injuries of competitive US figure skaters - King, D. L.; DiCesaro, S. F.; Getzin, A. R. (Cogent Medicine, 2017)
The majority of figure skaters are young females competing in local and regional competitions. There is little information describing injuries in this population of skaters. The purpose of this study was to describe injury characteristics and training habits of Non-Qualifying (NQ) and Qualifying (Q) competitive figure skaters and to compare their injury characteristics and training habits to Nationally or Internationally (NI) competitive figure skaters. 474 figure skaters completed the survey. 204 of these skaters met the criteria as currently competitive figure skaters participating in NQ, Q, or NI events. NQ skaters trained half as many hours per week (6.3 h/w) as compared to Q (12.3 h/w) and NI (13.7 h/w). There were 152 reported injuries across all groups. Acute injuries were more commonly reported than overuse injuries with ratios of 2.1:1 for NQ skaters; 1.3:1 for Q, and 1.4:1 for NI. Ankle sprains were the most common injury accounting for 11% of all injuries followed by concussion at 7%. Fractures/Stress fractures and concussions were more common in NI (17.6%, 11.7%) and Q (20.8%, 7.6%) than in NQ (12.4%, 2.15) skaters. NQ skaters predominantly reported acute injuries. Q and NI skaters have similar injury profiles to each other with more overuse injuries than NQ. Coaches and sports medical professionals need to be aware that skaters participating in qualifying competitions train similar hours and demonstrate similar injury patterns to elite skaters. While overuse injuries are more common in these skaters as compared to NQ skaters, acute injuries, particularly ankle sprains and concussions, dominate.